EMPLOYMENT OF STUDENTS GRADUATED FROM COMMERCIAL ENGINEERING UPE CDE HEADQUARTERS - Ramona Garcete Caballero, Ilza; Raquel González Doldán, Liliana; Carvallo Molas, Rossalía (Revista Gênero e Interdisciplinaridade, 2023)
In recent years, the number of professionals graduated from different Faculties with great knowledge to face a day-to-day job according to their abilities has increased remarkably. At present, the employment history of the students graduated from the Business Engineering Career of the Universidad Privada del Este, CDE Headquarters for the period 2016 and 2017 is not known, and the position they occupy in the market today and in what role is also unknown. they serve as graduates. A survey was carried out on 52 graduates of the Commercial Engineering career period 2016 and 2017, in which the researcher elaborates questions in an open and closed way, in order to know their professional activities and the opinion they have regarding their position. work, in order to obtain all the information possible, the approach used is the quantitative one to demonstrate the current performance of the students graduated from the period 2016 and 2017, with the help of the survey carried out we were able to identify that there are several students who are performing in his area as a Commercial Engineer.